Possible tax treatments of the transfer of accounting provisions during the sale of a business and subsequent tax considerations - Kroukamp, Susan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MAcc (Accountancy))--University of Stellenbosch, 2006.